Effect of foam glass granules fillers modification of lime-sand products on their microstructure - Jasińska Iga (Open Engineering, 2019)
Silicate products are products made exclusively from natural raw materials. A relatively high value of the heat transfer coefficient is still considered a fault. This property adversely affects the thermal insulation of buildings and energy consumption, so you should look for materials with a low heat conduction coefficient. One of the ways of obtaining such products can be the use of light, porous fillers in the mass of lime-sand products.